Passengers standing outside of White Pass and Yukon Railroad train car, White Pass, ca. 1907 - Nowell, Frank H., 1864-1950 (1907)
Caption on mount: Railroading Through the White Pass, Alaska On verso of image: ca. 1907 White Pass is located at the 2900 foot level on the Alaska-Canada boundary, 4 miles northeast of Mount Cleveland and 13 miles northeast of Skagway, in the Coast Mountains. This pass was on one of the principal routes to the Yukon taken by the prospectors during the Klondike Gold Rush 1897-1900. Although the White Pass route was less direct than the favorite but steeper Chilkoot Pass route, it was sued by more prospectors during the winter months.(pg. 1044) Notes from Donald Orth, Dictionary of Alaska Place Names: Geological Survey Professional Paper 567 (Washington: United States Government Printing Office, 1967) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number